MiR-143 Targets IGF-1R to Suppress Autoimmunity in Thyroid-Associated Ophthalmopathy - Tang W; Lv Q; Huang X; Li Y; Zou J; Zheng J; Sun L; Bao Y; Chen H; Li T; Zhang B; Xue S; et al. (Dove Medical Press, 2022)
Wei Tang,1,* Qian Lv,1,* Xiao Huang,2,* Yuzhen Li,2 JunJie Zou,1 Jiaoyang Zheng,1 Liangliang Sun,1 Yi Bao,1 Haiyan Chen,1 Tuo Li,1 Bei Zhang,1 Song Xue,1 Yan Song,1 Xingxing Zhang,1 Xiangfang Chen,1 Jiping Cai,2 Yongquan Shi1 1Department of Endocrinology, Second Affiliated Hospital of Naval Medical University, Shanghai, 200003, People's Republic of China; 2Department of Ophthalmology, Second Affiliated Hospital of Naval Medical University, Shanghai, 200003, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiangfang Chen; Yongquan Shi, Department of Endocrinology, Second Affiliated Hospital of Naval Medical University, No. 415 Fengyang Road, Huangpu District, Shanghai, 200003, People's Republic of China, Email chenxiangfang@smmu.edu.cn; young.stone@smmu.edu.cnObjective: Thyroid-associated ophthalmopathy (TAO) is an autoimmune disease that involves the remodeling of orbit and periorbital tissues. Thyroid-stimulating hormone receptor (TSHR) and insulin-like growth factor 1 receptor (IGF-1R) may stimulate the activation of autoimmunity in TAO, but the exact mechanism is unclear. We investigated whether IGF-1R/TSHR modulation in TAO may involve microRNA regulation.Methods: We conducted microarray analysis using RNA from the orbital connective tissue samples of 3 healthy and 3 patients with TAO. The involvement of differentially regulated microRNA in IGF-1R/TSHR modulation in TAO was evaluated in orbital fibroblasts (OFs) and female BALB/c mice.Results: Using hierarchical cluster analysis, we identified that miR-143 was downregulated in TAO. The expression levels of miR-143 in OFs were significantly reduced under IL-1B stimulation. However, OF proliferation and inflammatory responses decreased when miR-143 is overexpressed. In contrast, the suppression of miR-143 increased levels of inflammatory markers (IL-6, IL-8, MCP1) and hyaluronan accumulation. Moreover, overexpression of miR-143 significantly lowers levels of IGF-1R and TSHR. A luciferase assay indicated that miR-143 targets the 3'-UTR of IGF-1R. Increases in the expression of IGF-1R increased the expression of the inflammasome marker NLRP3 and apoptotic marker cleaved caspase-1; however, miR-143 overexpression decreased levels of IGF-1R, TSHR, NLRP3, cleaved caspase 1, IL-1B, and IL-18. In a mouse model of TAO, overexpression of miR-143 significantly reduced levels of IGF-1R and attenuated the adipogenesis associated with TAO.Conclusion: We found that miR-143 directly targets IGF-1R to alleviate the inflammatory response in TAO by indirectly decreasing levels of TSHR and inactivating NLRP3.Keywords: thyroid-associated ophthalmopathy, miR-143, thyroid-stimulating hormone receptor, insulin-like growth factor 1 receptor, NLRP3